Morphologic study of the efferent ductules of the pigeon (Columba livia) - Stefanini, M. A.; Orsi, A. M.; Gregorio, E. A.; Viotto, MJS; Baraldi-Artoni, S. M. (Wiley-Blackwell, 1999)
The efferent ductules of the pigeon are localized in the epididymal region and are topographically divided into proximal and distal, both portions being lined with stereociliated pseudostratified epithelium. Transmission electron microscopy shows five distinct cell types